Education For Sustainability: A Review-Based Perspective - Sinha, Rohit; Goel, Manisha; Sindhwani, Rajiv (Journal of Economics and Management, 2026)
The world is striving to achieve sustainable development by building an education system that offers youth the required knowledge and skills. This paper examines how the quality of education fosters skill improvement, digital literacy and global business. The study examines the evolution of education systems in relation to sustainable development. For the purpose of the study, a comprehensive analysis of academic literature, organizational publications and international policy frameworks has been conducted. The focus is on enhancements in employability and equitable economic growth. There is a huge gap between quality education and digital infrastructure required to achieve sustainable development. There are deficiencies in vocational and technical studies which affect employability and economic growth. There is need to enhance critical thinking, creativity and social mobility in education. The focus should be on employability skills, digital literacy, and inclusive infrastructure to achieve quality education and to promote equitable economic growth.